Prevalence of aggressive challenging behaviours in intellectual disability and its relationship to personality status: Jamaican study. (9th October 2013) - Tyrer, P.; Oliver, P.; Tarabi, S. A.
Abstract Background Both the classification of personality disorder in intellectual disability (ID) and its identification in practice are deemed to be difficult. A simpler approach to classification and its relationship to challenging behaviours were tested in an adult Jamaican population with ID. Method The study was carried out in Kingston, Jamaica, as part of a programme of field trials to determine the utility of the proposed revision of personality disorders in the 11th Revision of the International Classification of Diseases (ICD‐11), in a population of adults with ID living with their families or in supported care homes. Thirty‐eight people with borderline (n = 5), mild (n = 16), moderate (n = 14) and severe (n = 3) ID were assessed at face‐to‐face interview and with relatives or staff using the provisional criteria for severity of personality disorder and its associated domain traits, and challenging behaviour was assessed using the Problem Behaviour Check List (PBCL) (a 5‐point, 7‐item scale). Results Using the severity scale 18 patients (47%) had no personality disorder, 7 (18%) had personality difficulty, 9 (24%) had mild personality disorder, and 4 (11%) had moderate personality disorder. None of the sample had severe personality disorder in which there is high risk of harm to self or others. Of the four major trait domains, provisionally named anankastic, detached, emotional and dissocial, three were evenly distributed in those with personality disturbance with the antagonistic (antisocial) trait less commonly shown (6 only). Scores on the PBCL were higher in those with increasing severity of personality disorder (P = 0.03) and those in the antagonistic personality trait domain had the highest PCL scores. Conclusions Despite previous difficulties in assessing personality disorder in intellectual difficulties the ICD‐11 classification was easy to administer in practice in this population, and the higher problem behaviour scores in those with greater severity of personality disturbance support its construct validity.